2020
DOI: 10.1093/sysbio/syaa075
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of Parasitic and Nonparasitic Lice (Insecta: Psocodea): Combining Sequence Data and Exploring Compositional Bias Solutions in Next Generation Data Sets

Abstract: The insect order Psocodea is a diverse lineage comprising both parasitic (Phthiraptera) and non-parasitic members (Psocoptera). The extreme age and ecological diversity of the group may be associated with major genomic changes, such as base compositional biases expected to affect phylogenetic inference. Divergent morphology between parasitic and non-parasitic members has also obscured the origins of parasitism within the order. We conducted a phylogenomic analysis on the order Psocodea utilizing both transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 71 publications
6
58
0
Order By: Relevance
“…However, Johnson et al analyzed 1107 single-copy orthologous genes of 46 species and showed that the Philopteridae was monophyletic [ 45 ]. De Moya et al analyzed 2370 orthologous genes and also showed that Philopteridae was monophyletic [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Johnson et al analyzed 1107 single-copy orthologous genes of 46 species and showed that the Philopteridae was monophyletic [ 45 ]. De Moya et al analyzed 2370 orthologous genes and also showed that Philopteridae was monophyletic [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, any ectoparasite with PRRs similar to those of man might influence human immunity by the mechanism proposed here. Review of phylogenic emergence estimates of human ectoparasites [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and of IgE [ 59 ], however, indicates most ectoparasites could not have supplied the evolutionary pressure leading to the formation of IgE, Figure 4 . The Acari, on the other hand, predate emergence of IgE [ 58 ].…”
Section: Closingmentioning
confidence: 99%
“…Mt genome sequences are effective molecular markers to study the phylogenetic and systematic relationships at various taxonomic ranks across the phylum Arthropoda, including ectoparasites [41][42][43][44][45][46]. DNA sequencing provides the opportunity to further evaluate the phylogenetic relationships of the Philopteridae.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…However, Johnson et al analyzed 1107 single-copy orthologous genes of 46 species and showed that the Philopteridae to be monophyletic [43]. de Moya et al, analyzed 2,370 orthologous genes and showed that the Philopteridae to be monophyletic [44]. To date, the phylogenetic position of the Philopteridae in deep-level relationships within the order Phthiraptera could not be con dently determined.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%